Control interno y su relación con el cumplimiento de metas en la municipalidad distrital de Yarinacocha, 2020 - Rios García, Fernando Daniel (Universidad Nacional de la Amazonía Peruana, 2021)
The main objective of this study was to establish the relationship between internal control and the fulfillment of goals in the district Municipality of Yarinacocha, 2020; being a study of a non-experimental type and descriptive-correlational design, taking into account a population and sample of 24 collaborators from the aforementioned institution, for which the survey technique has been used and the questionnaire created from the dimensions and indicators of each variable; procedure and data analysis that led to conclude the following: It was determined that there is a significant relationship between internal control and the fulfillment of goals, a relationship established by the significance of 0.000 and a correlation coefficient of 0.873 which is considerable positive. Likewise, it was determined that there is a significant relationship between internal control and the fulfillment of specific individual goals, a relationship established by the significance of 0.000 and a correlation coefficient of 0.835, which is considerable positive. In addition, it was determined that there is a significant relationship between internal control and the fulfillment of operational goals, a relationship established by the significance of 0.000 and a correlation coefficient of 0.882, which is considerable positive. Finally, it was determined that there is a significant relationship between internal control and the fulfillment of official goals, a relationship established by the significance of 0.000 and a correlation coefficient of 0.894, which is considerably positive.

El presente estudio tuvo como objetivo principal establecer la relación entre el control interno y el cumplimiento de metas en la Municipalidad distrital de Yarinacocha, 2020; siendo un estudio de tipo no experimental y de diseño descriptivo – correlacional, teniendo en cuenta una población y muestra de 24 colaboradores de dicha institución antes mencionada, para la cual se ha utilizado la técnica de la encuesta y como instrumento el cuestionario creado a partir de las dimensiones e indicadores de cada variable; procedimiento y análisis de datos que llevo a concluir lo siguiente: Se determinó que existe relación significativa entre el control interno y el cumplimiento de metas, relación establecida por la significancia de 0,000 y un coeficiente de correlación de 0,873 la cual es positiva considerable. Asimismo, se determinó que existe relación significativa entre el control interno y el cumplimiento de metas específicas individuales, relación establecida por la significancia de 0,000 y un coeficiente de correlación de 0,835 la cual es positiva considerable. Además, se determinó que existe relación significativa entre el control interno y el cumplimiento de metas operativas, relación establecida por la significancia de 0,000 y un coeficiente de correlación de 0,882 la cual es positiva considerable. Por último, se determinó que existe relación significativa entre el control interno y el cumplimiento de metas oficiales, relación establecida por la significancia de 0,000 y un coeficiente de correlación de 0,894 la cual es positiva considerable.
Keywords: Auditoría de gestión; Administración pública; Gobierno local; http://purl.org/pe-repo/ocde/ford#5.02.04